Kajian biometrika daya saing antara varietas kedelai pada pertanaman campuran dan baris berseling=Intervarietal competition of soybeans planted in blend and alternate row : A biometrical study - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2000)
ABSTRAK Objective of the reported research was to quantify competition effect of five soybean varieties Lokon, Petek, Wilis, Cikuray and Dieng, selected based on their distinctive visual characters to facilitate separation at harvest. The five varieties were planted singly or in pair of equal proportion as blend or alternate row. It was arranged in 5 X 5 ballanced lattice Square design. Plot size was 4,8 m X 4,8 m with 40 cm inter row spacing and 20 cm within row spacing. Grain yield of each varieties were recorded from center row. Statistical analysis was done following McGilchrist (1965) and McGilchrist and Trenbath (1971). Data analysis showed that competition and depression effects of the five varieties were similar with respect to planting method. However mean depression which was significantly different from zero in blend turns out to be unsignificant in alternate row. Willis variety was a good competitor in blend but on the other hand Cikuray variety was a good competitor in alternate row. Analysis using McGilchrist and Trenbath practically led to similar conclusion.